Breeding a better stove: the use of computational fluid dynamics and genetic algorithms to optimise a wood burning stove for Eritrea - Burnham-Slipper, Hugh (2009)
Improved cooking stoves can bring significant benefits to women and children in rural African situations, due to reduced fuel consumption and improved indoor air quality. This investigation focuses on the use of Computational Fluid Dynamics (CFD) and Genetic Algorithms (GAs) to optimise a stove for Eritrea.